ANALISIS NILAI KARAKTER DONGENG DALAM â€œBUKU BUPENA KELAS IIIâ€ - Amin, Yuliana Fitri; Purwadi, Purwadi; Mudzanatun, Mudzanatun (JURNAL SINEKTIK, 2020)
The purpose of this research is to describe the character values in ?book bupena assessment for the elementary school class III? Muhammadiyah 11 Semarang. The approach used is descriptive approach is qualitative methods used to research in the condition of natural objects. Data collection techniques were carried out by triangulation data analysis was inductive and the qualitative research focuses more on the meaning of generalization. Technique data collection in this research was recorded to the note taking method. The problem is that the feasibility of the book is used as a guide for teachers and students in planting character values and how the value of fairy tale characters in the book. The results of this research that the fairy tales in the Bupena Assessment Book for Elementary / MI Class III especially Volume 3A are suitable to be used as a guide for teachers and students in planting character values containing 15 out of 18 character values with a percentage that is religious 1.9%, honest 12.6% , tolerance 7.8%, hard work 3.9%, creative 2.9%, independent 3.9%, democratic 1.9%, curiosity 10.7%, patriotism 2.9%, rewarding achievement 8.7%, friendly / communicative 12.6%, peace loving 6.8%, caring environment 5%, social care 12.6%, and responsibility 5.8%